Inversión y seguridad jurídica en Latinoamérica: ¿avance o retroceso? - Dromi, Roberto; Amado Vargas, José Daniel; Bullard Gonzáles, Alfredo; Quiñones Alayza, María Teresa; Danós Ordoñez, Jorge (Advocatus, 2005)
No presenta resumen